Empowering Farm Women Through Income and Livelihood Generation - Das, J. K. (International Journal of Bio-resource and Stress Management, 2014)
Women empowerment covers many influencing factors wherein decision making power as an important indicator generally comes from the economic contribution; economic contribution of women through the access of livelihood generation puts forward the importance of women in the family and society at large. The present study is an endeavor to identify the different independent variables of on-farm and off-farm activities from where their power of empowerment emerges. The study was conducted in area under Haringhata Panchayat Samity, West Bengal with a total sample size of 100 in 5 selected Mouzas randomly. The statistical tools applied were correlation, multiple regression, path analysis, chi-square test, paired t-test and canonical correlation. It is observed that the variables like age, material possession, mass media exposure, family income and socio-economic status have got the important bearing on the gain in empowerment of women.